Strategy For Improving the Quality of Public Services in the Personnel Affairs and Human Resource Development Division (BKPSDM) Of Kaimana Re-gency - Ira Tuankotta; Sri Kamariyah; Sri Roekminiati (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2026)
This research seeks to examine methods for enhancing the quality of public services at BKPSDM Kaimana Regency, focusing on both facilitating and hindering elements in their execution, innovation in services, the efficiency of personnel administration management, and the responsiveness of public officials in addressing user needs. This study utilized a qualitative method featuring a descriptive research framework. The research was carried out at BKPSDM Kaimana Regency. Data were gathered via observation, detailed interviews, and documentation. The research informants included BKPSDM leaders, administrative service personnel, and civil servants who utilized the services. Data were examined through an interactive analysis framework that included data reduction, data presentation, and the formulation of conclusions. The results show that BKPSDM Kaimana Regency has executed various strategies to enhance public service quality by developing employee skills, streamlining service processes, improving internal coordination, and leveraging information technology for personnel management. Service innovation was implemented via digital communication and enhanced administrative management to boost service effectiveness. The responsiveness of public officials also demonstrated favorable improvements with more communicative and accessible services tailored to users’ needs. Nonetheless, the execution of public services continues to encounter multiple challenges, such as restricted digital infrastructure, geographical factors, insufficient human resources, and a lack of technological skills among staff. This research demonstrates that enhancing public service quality necessitates collaboration among strengthening human resources, innovating services, and creating adaptive bureaucratic systems to react to public service reform.